Can Illness Perceptions Predict Lower Heart Rate Variability following Acute Myocardial Infarction? - Princip, Mary; Scholz, Marco; Meister-Langraf, Rebecca E.; Barth, Jürgen; Schnyder, Ulrich; Znoj, Hansjörg; Schmid, Jean-Paul; Thayer, Julian F.; von Känel, Roland (Frontiers in Psychology, 2016)
Objective: Decreased heart rate variability (HRV) has been reported to be a predictor of mortality after myocardial infarction (MI). Patients' beliefs and perceptions concerning their illness may play a role in decreased HRV. This study investigated if illness perceptions predict HRV at 3 months following acute MI. Methods: 130 patients referred to a tertiary cardiology center, were examined within 48 h and 3 months following acute MI. At admission, patients' cognitive representations of their MI were assessed using the German version of the self-rated Brief Illness Perception Questionnaire (Brief IPQ). At admission and after 3 months (follow-up), frequency and time domain measures of HRV were obtained from 5-min electrocardiogram (ECG) recordings during stable supine resting. Results: Linear hierarchical regression showed that the Brief IPQ dimensions timeline (β coefficient = 0.29; p = 0.044), personal control (β = 0.47; p = 0.008) and illness understanding (β = 0.43; p = 0.014) were significant predictors of HRV, adjusted for age, gender, baseline HRV, diabetes, beta-blockers, left ventricular ejection fraction (LVEF), attendance of cardiac rehabilitation, and depressive symptoms. Conclusions: As patients' negative perceptions of their illness are associated with lower HRV following acute MI, a brief illness perception questionnaire may help to identify patients who might benefit from a specific illness perceptions intervention.